UNDERSTANDING SOCIAL ASPECTS IN SPINAL OSTEOCHONDROSIS PATIENTS - Bakhromjon M. Mamatqulov; Dilorom A. Umurzakova (Central Asian Journal of Medicine, 2025)
The article explores the impact of social factors on the development of osteochondrosis. The research was carried out using an analytical approach, including case -control method. The sample consisted of 230 participants in each group, ensuring the reliability of the collected data. Information on the respondents’ average age, gender distribution, education level, and occupations is provided. The study also examined participants’ marital status, number of children, and average income. The findings reveal a correlation between social factors and the risk of osteochondrosis, highlighting the importance of considering social aspects in the prevention and treatment of spinal disorders.